The bubble wrap boy - Earle, Phil (Delacorte Press, 2015)
Fourteen-year-old social outcast Charlie Han, known as "the short Chinese kid" at school, searches for a talent to improve his popularity, but when he discovers skateboarding, much to the disapproval of his overprotective mother, he also uncovers a huge family secret.
"Originally published in hardcover by Penguin Books, London, in 2014"--Title page verso.
Keywords: Coming of age -- Fiction; Secrets -- Fiction; Family life -- Fiction; Friendship -- Fiction; Skateboarding -- Fiction; Chinese -- England -- Fiction